Hydrolytic Potential of Talaromyces thermophilus β-Xylosidase and Its Use for Continuous Xylose Production - Ines Maalej-Achouri; Hafedh Belghith; Mohamed Guerfali (Food Technology and Biotechnology, 2013)
We report here the enhanced hemicellulase production by a Talaromyces thermophilus strain in a fed-batch fermentation using 3.6-litre laboratory-controlled bioreactor. When grown on wheat bran, this fungus produces a wide spectrum of polysaccharide-hydrolysing enzymes, mainly endo-β-1,4-xylanase (27 U/mL), β-xylosidase (1.4 U/mL), α-L-arabinofuranosidase (1.05 U/mL) and β-D-mannosidase (0.78 U/mL). The β-xylosidase was purified and shown to hydrolyse xylobiose and short xylooligosaccharides, but it was inactive on xylan. It released xylose from xylooligosaccharides with a degree of polymerisation ranging from 2 to 5. Talaromyces thermophilus β-xylosidase activity was unaffected by high glucose or arabinose concentration (0.5 M) and retained 75 % of its original activity in the presence of 133 mM xylose. Chitosan-immobilised β-xylosidase was used in a continuous process of conversion of wheat bran hydrolysate to xylose in a packed bed reactor. Xylose production of 18.6 mg/g was reached after six hours in the bioreactor and was twofold higher than that produced by the free enzyme. The produced xylose was further converted into xylitol using the crude intracellular enzyme of Talaromyces thermophilus.